PERCOBAAN PEMBUNUHAN SEBAGAI MAWANI‘ AL-IRTH DALAM KHI PASAL 173 DILIHAT MENURUT PERSPEKTIF MAQASID Al-SYARI‘AH - Mawaddah, Lailatul (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Agama Islam Jamiatut Tarbiyah Lhoksukon, 2022)
Trial of Assassination is an action carried out with the intention of killing people, but the person who wants to be killed does not die. In KHI Article 173 stated that the trial of assassination were prevented from inheriting, but in fiqh did not mention this, because that was the result of ijtihad by Indonesian Islamic law experts. Based on this, this research attempted to explain the provisions of the KHI regarding the trial of assassination as mawani' al-irth, and the provisions of KHI regarding the trial of assasination as mawani‘ al-irth seen in the motivations behind it. Both of these will be studied using the perspective of maqasid al-syari'ah. The type of research used in this thesis is library research (qualitative research). Sources of data from this study come from the book al-Muwafaqat, Tasyri 'al-Jinaai al-Islami, Al-Fatawa al-Fiqhiyyah al-Kubra, Al-Tahzib fi Fiqh Imam Al-Syafi'i and the book Compilation of Islamic Law by Cik Hasan Bisri, as well as books and journals relating to maqasid al-syari'ah and mawani' al-irth. Data collection method is carried out in documentation and data analysis method in the form of qualitative descriptive. The results of the study indicate that the provisions of the KHI Article 173 concerning trial of assassination that’s hindered from inheriting is not suitable to be applied. Because the trial of assassination does not cause a person to die. Then in KHI also do not recognize the term forgiveness, even though the opportunity to be forgiven by the own heir is very large. Furthermore, in KHI, it does not consider the background of doing this action, even though between one person and another person has different intentions and objectives. Although the trial of assassination is a case that violates the existence of maqasid al-syari‘ah from the needs of the dharuriyyah, which is guarding the soul (hifz al-nafs), the benefit here is to apply a law according to the conditions that it wants. Because the basic purpose of Islamic law (maqasid al-syari‘ah) is to gain benefit and prevent damage (mafsadah).